Comparative risk assessment of oil spill response options for a deepwater oil well blowout: Part II. Relative risk methodology. (August 2018) - Bock, Michael; Robinson, Hilary; Wenning, Richard; French-McCay, Deborah; Rowe, Jill; Walker, Ann Hayward
Abstract: Subsea dispersant injection (SSDI) was a new oil spill response (OSR) technology deployed during the Deepwater Horizon accident. To integrate SSDI into future OSR decisions, a hypothetical deepwater oil spill to the Gulf of Mexico was simulated and a comparative risk assessment (CRA) tool applied to contrast three response strategies: (1) no intervention; (2) mechanical recovery, in-situ burning, and surface dispersants; and, (3) SSDI in addition to responses in (2). A comparative ecological risk assessment (CRA) was applied to multiple valued ecosystem components (VECs) inhabiting different environmental compartments (ECs) using EC-specific exposure and relative VEC population density and recovery time indices. Results demonstrated the added benefit of SSDI since relative risks to shoreline, surface wildlife and most aquatic life VECs were reduced. Sensitivity of results to different assumptions was also tested to illustrate flexibility of the CRA tool in addressing different stakeholder priorities for mitigating the impacts of a deepwater blowout. Graphical abstract: Unlabelled Image Highlights: Subsea dispersant injection (SSDI) can be added to oil spill response (OSR) options. CRA tool assists decision-maker evaluating relative risk trade-offs of OSR options. Oil spill model quantified exposure for a hypothetical deepwater oil spill. Relative densities and recovery times with exposure quantify relative risks. Inclusion of SSDI reduced risks to wildlife, shorelines and most aquatic life.